Evaluating the Role of Community-Based Organizations in Adolescent Sexual and Reproductive Health Education and Early Pregnancy Prevention in Makoko, Yaba LCDA - Chukelu, C. N. (Journal of Research in Adult and Continuing Education, 2025)
Adolescent reproductive health remains a pressing public health challenge in low and middle income countries, where early pregnancies contribute significantly to maternal and neonatal mortality. Despite global efforts, barriers such as stigma, financial constraints, and cultural restrictions continue to limit adolescents’ access to sexual and reproductive health (SRH) services. This study evaluates role of community-based organizations in adolescent sexual and reproductive health education and early pregnancy prevention, focusing on Yaba Local Council Development Area (LCDA) Makoko. Using a cross-sectional survey design, data were collected from 372 adolescent girls (aged 10–19) through structured questionnaires. Findings revealed a moderate level of SRH knowledge among respondents, with notable gaps in contraceptive awareness (mean score = 2.60) and service accessibility (mean = 2.39). While CBO-led programs improved awareness (mean = 2.74), participation rates remained low (mean = 2.37), and persistent barriers including fear of judgment (mean = 3.03), cost (mean = 3.18), and cultural restrictions (mean = 2.87) hindered service utilization. The study underscores the potential of CBOs in bridging SRH education gaps but highlights the need for enhanced community engagement, youth-friendly services, and policy integration to address structural barriers. Recommendations include expanding peer-led education, subsidizing SRH services, training healthcare providers in adolescent-friendly care, and advocating for inclusive national policies. By leveraging CBOs’ community trust and adopting multi-sectoral strategies, stakeholders can significantly improve adolescent SRH outcomes in Nigeria.